Intrafetal Interventional Procedures and Anesthetic Implications - Nancheva, Jasminka; Kiprijanovska, Biljana; Nancheva Bogoevska, Andrea; Elenova, Biljana; Sivakov, Borche (Department of Anaesthesia and Reanimation, Faculty of Medicine, Ss. Cyril and Methodius University in Skopje, R.N. Macedonia, 2024)
Intrafetal surgery is an operative procedure which is performed on a pregnant mother to treat her baby before it is born. Maternal-fetal surgery can occur either during the middle of pregnancy or at the end of the pregnancy. In all cases, anesthesiologists are involved to provide for the comfort and safety of pregnant mothers and their babies. As these defects and malformations have become more readily identified, the number of innovative therapies has also amplified. Rapid advances in imaging techniques and prenatal diagnosis have allowed for the progressive development of prenatal interventions and surgeries and today they have become an integral part of the management of high-risk pregnancies. In addition, the rapidly growing capability of digital optics and miniaturized instrumentation has now allowed fetoscopy procedures to become a reality. There are 3 basic types of surgical interventions: 1. Minimally invasive midgestational procedures, 2. Midgestational open procedures, 3. Ex-utero intrapartum treatment (EXIT). These procedures require many manipulations and monitoring in both the mother and the unborn fetus. The combination of underdeveloped organ function and usually life-threatening congenital malformation places the fetus at considerable risk. Fetal surgery also leads to enhanced surgical and anesthetic risk in the mother including hemorrhage, infection, airway difficulties and amniotic fluid embolism, so anesthetic management should focus on maintaining adequate uteroplacental blood flow, optimizing surgical conditions, and minimizing maternal and fetal risk.
Keywords: maternal-fetal surgery; fetoscopy; ultrasound guided procedures